Current Developments of Legal Instruments to Prevent and Control of Pollution In The Straits of Malacca - Pulung Widhi Hari Hananto (Administrative Law and Governance Journal, 2019)
The Strait of Malacca is one of the busiest straits in the world, with more than 60,000 vessels through the strait per year. This strait is located in a strategic location to connect the west part and east part of the world. However, the number of vessels transit and pass through the strait affects marine environmental issues. Pollution, especially vessel-based sources, may affect marine life. To settle the issues along with the boundary issue, Indonesia, Malaysia, and Singapore have entered into some agreements to cooperate to manage the Strait of Malacca since the 1970s. Recently, the concept of Cooperative Mechanism has been developed. Several meetings amongst these states have been done with some positive deals. With this concept, the littoral states believe that it can prevent, reduce, and control of marine pollution in the Strait of Malacca. However, more progress is still needed to enhance from the implementation of the Cooperative Mechanism. Keywords: Strait of Malacca, Pollution, Marine, Environment, Cooperative Mechanism.